Attitude and decisions regarding personal healthcare: the case of women under microfinancein Edo state, Nigeria (2020)
The paper examined women’s attitude towards their personal health using the Health Belief Model as theoretical framework. Questionnaire was administered to 750 purposively selected respondents consisting of 400 from 3 branches of a microfinance banks (MBs) with integrated health services (IHS), and 350 from 3 other MBs without IHS in Edo state Nigeria. Key Informant Interviews (KIIs) were conducted with 20 microfinance officials. Questionnaire was administered to 750 purposively selected respondents consisting of 400 from 3 branches of a microfinance banks (MBs) with integrated health services (IHS), and 350 from 3 other MBs without IHS in Edo state Nigeria. Twenty Key Informant Interviews (KIIs) were conducted with microfinance officials. Women displayed positive attitude towards their personal health with mean score for clients in both MBs with IHS and without IHS being 63.9±8.2 and 47.9±5.6 respectively (where mean score for positive attitude is ≥ 40). Furthermore, although 62.0% agreed “they cannot take their health for granted no matter what”, those who agreed and were undecided that “they won’t make decisions about their health without their spouses” were 47.8% and 32.8% respectively. Women’s roles as caregivers and dependants on their spouses make them prioritize their household needs and spouses’ decision over their personal health. Enlightening women on the relevance of prioritizing their personal healthcare is recommended to reduce poor health conditions among women.